EXAMINATION AND ASSESSMENT OF CHILDREN'S PHYSICAL DEVELOPMENT. (Лучшие интеллектуальные исследования, 2025)
Abstract : The physical development of children and adolescents is one of the most important indicators of health. The physical development of children is determined together with the state of health of children during in-depth medical examinations of children's institutions, teenage rooms and other children's institutions.